2016
DOI: 10.1074/jbc.m116.729210
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Correlation between Infectivity and Gp120 Density on HIV-1 Virions Revealed by Optical Trapping Virometry

Abstract: The envelope glycoprotein (Env) gp120/gp41 is required for HIV-1 infection of host cells. Although in general it has been perceived that more Env gives rise to higher infectivity, the precise quantitative dependence of HIV-1 virion infectivity on Env density has remained unknown. Here we have developed a method to examine this dependence. This method involves 1) production of a set of single-cycle HIV-1 virions with varied density of Env on their surface, 2) site-specific labeling of Envspecific antibody Fab w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 40 publications
(61 reference statements)
1
37
0
4
Order By: Relevance
“…A previous study has shown that increasing Env from less than one gp120 molecule per virion to an average of nine increased the infectivity of HIV-1 (49). We find that V1, V2, V3, and V4 hVLPs (ranging from an average of 49 to 127 spikes per virion) are equally infectious and ϳ20-fold more infectious than normal pseudovirus that averages ϳ0.5 spikes per virion.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A previous study has shown that increasing Env from less than one gp120 molecule per virion to an average of nine increased the infectivity of HIV-1 (49). We find that V1, V2, V3, and V4 hVLPs (ranging from an average of 49 to 127 spikes per virion) are equally infectious and ϳ20-fold more infectious than normal pseudovirus that averages ϳ0.5 spikes per virion.…”
Section: Discussionmentioning
confidence: 55%
“…Virion particles were modeled using cellPACK, an open-source project (http://cellPACK.org) designed to assemble large-scale models from molecular building blocks, as previously described (45,46). With the number of spikes (10,49,127,214, and 330) and particle size (140 nm) provided as input, cellPACK randomly distributed spikes on the surface of the spherical particle.…”
Section: Antibodies and Cells Monoclonal Antibodies (Humanmentioning
confidence: 99%
“…However, even when diffusion is bypassed, the efficiency to form specific virion-cell contact is low, suggesting that other barriers instead of diffusion limit virion infectivity. These potential barriers include the envelope glycoprotein density on individual virions [19], and also the density and distribution of receptors on individual host cell surface, the impact of which on viral attachment can be investigated systematically using current experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…The density of HIV gp120 tested on the SLBs was established in our previous studies (28). For comparison, the estimated Env density on the surface of HIV virions is 8 to 14 Env spikes per virion (36,37), which correspond to 250 to 450/m 2 for virions with a diameter of ϳ100 nm. On the cell surface, the HIV Env glycoproteins are expressed in patches (38,39), and the confocal microscopy measurements of the local densities of HIV gp120 at such patches on the HIV Env-transfected cell surfaces yielded an average density of 369 (median, 287; range, 0 to 2,490) molecules/m 2 (reference 28 and data not shown).…”
Section: Cellsmentioning
confidence: 99%